Gramaticalização de até : usos na linguagem padrão dos séculos XIX e XX - Rosário, Ivo da Costa do (2007)
Analysis of the item até (until) in the standard language, in the XIX and XX centuries, both in brazilian and lusitanian Portuguese, based on the North-American Functionalist Linguistics theoretical line. Investigation based on the hypothesis of Heine et alii (1991) and in the localist theory of Lyons (1980), that defend that the item até (until) has been grammaticalized in the perspective of a path SPACE > TIME > TEXT. Corpora proceeding from three textual genders (news, announcement and editorial). Proposition of three functional patterns of use of the researched item, defined in prototypical categories: a) spacial uses, the most basic, in general already decreasing in terms of use, due to its more primitive origin. They remain with more strength in the news; b) temporal uses, the most frequent and productive in our synchrony, used especially in announcements and news; c) notional uses, the more innovated, representing more grammaticalized uses, more present in editorials and announcements.